Caesarean scar ectopic pregnancy: a case report. (May 2014) - Sieczko, Dominic; Edwards, Hazel; Heggs, Karen; White, Donna
This case study discusses a recent diagnosis of a rare form of ectopic pregnancy within a Caesarean section scar. Evidence indicates that the prevalence of this form of ectopic pregnancy is escalating due to the increasing number of Caesarean sections performed. As ultrasound plays a major role in diagnosing this rare life-threatening condition, we recommend key points for practitioners to consider for meticulous assessment and accurate diagnosis.